Use of Loose Part Media With Cardboard and Sand Materials in Islamic Children's Schools - Mirroh Fikriyati; Sri Katoningsih; Sabbir Hasan (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2023)
The purpose of this study is to describe the use of loose parts media made from cardboard and sand in learning at the Islamic Children's School TKIT Permata Hati Kartasura Sukoharjo. The research subjects were teachers, informants such as school leaders, and students. Data collection techniques with interviews, observation, and documentation. While the data analysis with the stages of data reduction, data presentation, drawing conclusions, and verification, namely drawing conclusions and verifying the collected data. The results showed that loose parts media designed in ships and simple musical instruments have successfully stimulated the growth of 6 aspects of child development. Aspects of Moral Religion Values with the introduction of seawater that ships pass as a creation of God. Gross motoric physical aspects such as rowing. Physical aspects of fine motor skills include feeling the smooth and rough parts of the ship. A cognitive aspect with counting the number of doors, windows, and stairs on the boat. A language aspect with mentioning the vowel letters on the ship. Aspects of Social Emotional like patiently waiting for their turn in holding the boat. An aspect of art with hearing, imitating, and singing songs about ships. It is also strengthened by playing a musical instrument from a bottle filled with sand.